If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-6x+5=3x+6-4x
We move all terms to the left:
2x-6x+5-(3x+6-4x)=0
We add all the numbers together, and all the variables
2x-6x-(-1x+6)+5=0
We add all the numbers together, and all the variables
-4x-(-1x+6)+5=0
We get rid of parentheses
-4x+1x-6+5=0
We add all the numbers together, and all the variables
-3x-1=0
We move all terms containing x to the left, all other terms to the right
-3x=1
x=1/-3
x=-1/3
| 8w=-1/7 | | 7.2(x-2.75)=-14.5= | | |6x-1|+2=2 | | 3r-16=5 | | -3(x+4)-3x=7 | | 7p+2=37 | | (7n+3)/4-6=3.5 | | 3(x-4)(x-4)=27 | | 100=22s+56 | | (6+x)^2=108 | | 4v=8=26-2v | | n/10+5=45 | | 5-(9/t)=-4/t^2 | | x=224/(1+9/100) | | 6d*2=5.2 | | -21w-10=24w+3 | | 13=x/3+2 | | x(x+2)=x2+2 | | (x+4)^2-5=0 | | X/10-7=9x= | | 2-7n=16 | | (6x-8)=(5x+14) | | 1/6x-(1/7x)+1/42x=6 | | -(v-4)=-6v+16 | | 79.8=7(m+3.8 | | 2n-7n=16 | | -2x+4=-2x+6 | | 3x+38+5x-32=180 | | 7x-(6)=36 | | -10(-2)+y=4 | | 1=-3w+64 | | -106+3x=38+9x |